Palinomorfos continentales y marinos de la Formación Monte León en su área tipo, provincia de Santa Cruz, Argentina - Barreda, Viviana Dora (2000)
The palynomorph content of surface samples frorn two sections –Monte Observación and Monte Entrada- crapping out at the Atlantic coast in Santa Cruz Pravince is analysed herein. Poorly to fairly well preserved terrestrial and marine assemblages were recovered. The abundance and diversity of the palynoflora show strang paleoenviranmental control, fluctuating from moderate to low as a reflection of near shore to inner neritic depositional conditions. A Miocene (probably Early Miocene) age is assigned to the sections on the basis of the stratigraphic range of selected species previously recorded in nearby areas. The sections can be partly correlated, a1though the uppermost levels of the Monte Observación section, mostly deposited in a freshwater environment, were not encountered in Monte Entrada section. These upper levels represent the transition to the overlying continental Santa Cruz Forrnation. A tectonic reactivation event was recognised in both sections, characterised by a suddenincrease of reworked palynomorphs, mostly frorn Upper Cretaceous deposits from the source area of the sediments.